2022
DOI: 10.26710/jafee.v8i3.2451
|View full text |Cite
|
Sign up to set email alerts
|

Level of Awareness and Understanding towards Money Mule Among Malaysian Citizens

Abstract: Objective: Money mule is a bank account used by another person unknowingly or voluntarily by the owner of the account to obtain a reward or by fraudulent means for illegal or illegal financial transactions. Syndicates usually get these mule accounts (also known as surrogate accounts) by deceiving those who need extra income and have a low level of financial literacy. This study will determine the level of awareness towards money mule and understanding towards the dangerous of money mule. In this research, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…A systematic review reported that the overall awareness among Malaysians of money mule activities is low (Ilyas et al, 2022). However, a quantitative survey of 391 respondents reported a high https://doi.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review reported that the overall awareness among Malaysians of money mule activities is low (Ilyas et al, 2022). However, a quantitative survey of 391 respondents reported a high https://doi.…”
Section: Introductionmentioning
confidence: 99%